Zakat Fund Allocation Conflict: Obstacles to Financing Single Tuition Fees for Mustahik Students - Hadi Syahputra (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2026)
The implementation of zakat fund scholarships for the Single Tuition Fee (UKT) of underprivileged students at IAIN Langsa faces serious challenges due to a structural conflict between the Shariah distribution mandate to the eight asnaf (recipients) and the real constraints of collected funds. Theoretically, this limitation is a manifestation of the Zakat Fiscal Gap at the regional level, where the potential for zakat collection significantly exceeds its realization, severely restricting the resources available for education programs (fii sabilillah) (Badruddin 2019). This fiqh allocation conflict is compounded by internal governance policies, specifically selection criteria based on the Grade Point Average (IPK), which tends to prioritize academic accountability over the distributive justice principle to the most needy mustahik, and the weak post-disbursement monitoring and evaluation (monev) mechanism that hinders the measurement of the program's real impact (Nurrahmat et al. 2023). This policy study utilizes a qualitative approach involving document analysis, supported by the theoretical frameworks of Fiqh Asnaf, Zakat Fiscal Gap Theory, and Sustainable Social Financing Theory. In-depth analysis using root-cause analysis identified the primary root problem as fund inadequacy due to the fiscal gap and unresolved fiqh allocation conflict. There is an urgent need to balance the Shariah goal of poverty alleviation with the managerial needs of educational institutions. After scoring various policy alternatives, the best option is the Regulation on the Progressive UKT Cost-Sharing Scheme based on Poverty Level. This scheme is deemed most optimal as it ensures the largest portion of the zakat subsidy is directed towards students in the extreme poverty category, effectively addressing the issues of equity and fund sufficiency. Therefore, the recommended policy solution is a Joint Decree on Prioritizing Zakat Fii Sabilillah Allocation for Human Resource Investment and integrating the progressive cost-sharing scheme to create a sustainable, equitable, and impact-oriented educational financing model.